External Finance, Sudden Stops, and Financial Crisis : What is Different This Time? - Ozkan, F. Gulcin (IMF Working Papers; Working Paper ;, 2010)
This paper develops a two-country DSGE model to investigate the transmission of a global financial crisis to a small open economy. We find that economies hit by a sudden stop arising from financial distress in the global economy are likely to face a more prolonged crisis than sudden stop episodes of domestic origin. Moreover, in contrast to the existing literature, our results suggest that the greater a country's trade integration with the rest of the world, the greater the response of its macroeconomic aggregates to a sudden stop of capital flows.